The role of notarial archive in conducting of a notary services in Republic of Kazakhstan - Urisbayeva, A.A.; Assubayeva, A.S. (Journal of actual problems of jurisprudence, 2018)
Archive- is a centre of historical memorials and one of the main state means which preserves historical and cultural heritage, fulfills social, legal, political, scientific and moral needs of the society. Among other archives, the areas of activities of the branch of Notary Chamber «Private notarial archive» include storage of the notary documents of private notaries, assurance of the preservation of documents, their usage in the interests of the country, society and people, maintenance of documents’ register, provision of information support for organizations and citizens, carrying out methodical works with private notaries in respect of archiving and documentation, development of methodological materials for private notaries. Key words: Archive, State archive fund, Private notarial archive, documents, files’ nomenclature.